What are The Predictor Factors of Teacher Work Stress? A Systematic Literature Review 2015-2025 - Annissa Fitriani Rizka; Nurhattati Fuad; Siti Zulaikha; Kamaludin Kamaludin (Journal of Educational Sciences, 2026)
The phenomenon of teacher work stress is increasingly becoming a concern due to increasing professional demands and the dynamics of change in the education system. This study aims to identify predictors of teacher work stress through a systematic review of published literature from 2015–2025. The research method used is a Systematic Literature Review (SLR) approach based on the PRISMA protocol with the stages of identification, selection, quality evaluation, and synthesis of findings. From all the studies reviewed, a number of literatures showed that workload and work environment are two main determinants that consistently contribute to increased teacher work stress. High workload, especially related to administrative tasks and dual responsibilities, has been shown to increase psychological distress, while an unsupportive work environment amplifies the impact of stress and reduces teacher well-being. The results of this study confirm that work stress arises in response to an imbalance between job demands and available resources, therefore, comprehensive management efforts are needed. In conclusion, workload and work environment play a significant role as triggers of teacher work stress, and these findings can form the basis for developing policies and intervention strategies to create a healthier and more sustainable educational work climate.